Strengthening Strategy to Religious Moderation at Indonesian Universities - Nasih, Ahmad Munjin; Thoriquttyas, Titis; Sultoni, Achmad; Malihah, Elly; Azca, Muhammad Najib; Budiman, Riadi (Journal of Ecohumanism, 2024)
Various mentoring programs in higher education have been globally explored to address issues of radicalism and intolerance. However, there was a notable lack of investigation within the context of tertiary education in Indonesia. This study aimed to qualitatively examine the implementation of Islamic mentoring programs in three Indonesian universities. The study was conducted at Universitas Pendidikan Indonesia (UPI), Universitas Negeri Malang (UM), and Universitas Tanjungpura (UNTAN). Data were collected through observations, documentation, and interviews with university stakeholders responsible for managing these programs. The study employed a qualitative approach to gather in-depth insights into implementing the mentoring programs. The findings revealed that each university integrated the principles of religious moderation into their mentoring programs despite their unique orientations and curricula. The mentoring programs aimed to foster Islamic brotherhood under Pancasila, Indonesia's foundational philosophical theory. Each university developed distinct approaches to mentoring that reflected their individual objectives, activities, and curricular designs. These findings provide valuable insights for policymakers to develop more effective strategies for implementing mentoring programs that promote religious moderation in Indonesian universities. The study highlighted the importance of tailored approaches to accommodate each institution's diverse needs and contexts, ensuring the programs' effectiveness in promoting peace, tolerance, and social cohesion.